The plot chickens - Auch, Mary Jane. (New York : Holiday House, 2009)
Henrietta the chicken loves to read so much that she decides to write a book herself, but first no one will publish a book written by a chicken, and then, when she publishes it herself and it gets a terrible review in "The Corn Book," Henrietta is devastated.
Keywords: Chickens -- Fiction; Authorship -- Fiction; Humorous stories